2018
DOI: 10.1098/rspb.2017.2733
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of insect–yeast relationships and its relevance to human industry

Abstract: Many species of yeast are integral to human society. They produce many of our foods, beverages and industrial chemicals, challenge us as pathogens, and provide models for the study of our own biology. However, few species are regularly studied and much of their ecology remains unclear, hindering the development of knowledge that is needed to improve the relationships between humans and yeasts. There is increasing evidence that insects are an essential component of ascomycetous yeast ecology. We propose a 'disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
114
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 115 publications
(120 reference statements)
1
114
0
1
Order By: Relevance
“…), yeast‐mediated changes in olfactory bouquets may improve food location by bumble bees and thus reduce the allocation of resources devoted to find suitable nectar patches (Madden et al. ). Our foraging data suggest that addition of C. bombiphila and M. gruessii , two yeast species that increase bumble bee fitness, did not affect the foraging behavior of the bees, indicating that bumble bees do not perceive inoculated nectar as beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), yeast‐mediated changes in olfactory bouquets may improve food location by bumble bees and thus reduce the allocation of resources devoted to find suitable nectar patches (Madden et al. ). Our foraging data suggest that addition of C. bombiphila and M. gruessii , two yeast species that increase bumble bee fitness, did not affect the foraging behavior of the bees, indicating that bumble bees do not perceive inoculated nectar as beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Most insect pollinators are well equipped to detect and recognize microbial infestation of food sources (Fouks and Lattorff ), and yeasts have been hypothesized to provide an honest signal (via volatiles) to plant visitors of sugar‐rich microsites (Madden et al. ). For example, behavioral tests under both controlled greenhouse conditions and field conditions have shown that bumble bees generally prefer nectar inoculated with Metschnikowia reukaufii over non‐inoculated nectar (Herrera et al.…”
Section: Introductionmentioning
confidence: 99%
“…While Drosophila in the melanogaster subgroup breed in fruit, they derive an array of fitness benefits from consuming yeasts which include influences on sexual receptivity (Gorter et al, ), fecundity and larvae development (Buser et al, ; Rohlfs & Kürschner, ) and other life history traits (Anagnostou, Dorsch, & Rohlfs, ). It is therefore unsurprising that at least D. melanogaster and Drosophila simulans are strongly attracted to certain yeast‐derived volatiles (Becher et al, ; Buser et al, ; Günther, Goddard, Newcomb, & Buser, ; Madden et al, ; Stökl et al, ). Yeasts metabolize fruit precursors to produce energy and biomass, but also release a range of yeast volatile organic compounds (YVOCs) as they do so (Cordente, Curtin, Varela, & Pretorius, ; Hazelwood, Daran, Maris, Pronk, & Dickinson, ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of fungal volatiles as semiochemicals attracting insects is well described (Beck & Vannette, 2017;Madden et al, 2018) and Saccharomycetaceae (budding) yeasts and Drosophila flies in the "melanogaster" subgroup (Clark et al, 2007) are not only influential research models but also co-inhabit economically important fruit crops (Hamby, Hernandez, Boundy-Mills, & Zalom, 2012;Lam & Howell, 2015) where certain Drosophila species (such as D. suzukii) may act as nuisance and damaging pests (Walsh et al, 2011), and yeasts may variously have negative, benign or positive impacts on fruits or their fermented products (Gschaedler, 2017;Suh, Blackwell, Kurtzman, & Lachance, 2006). While a variety of Saccharomycetaceae yeast species are found associated with fruits (Masneuf-Pomarede, Bely, Marullo, & Albertin, 2016;Taylor, Tsai, Anfang, Ross, & Goddard, 2014), they are also found in a range of other niches (Gayevskiy & Goddard, 2016;Morrison-Whittle, Lee, & Goddard, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation